2022
DOI: 10.3390/ijms23052532
|View full text |Cite
|
Sign up to set email alerts
|

Doxycycline Decreases Atherosclerotic Lesions in the Aorta of ApoE-⁄- and Ovariectomized Mice with Correlation to Reduced MMP-2 Activity

Abstract: Atherogenic events promote changes in vessel walls, with alteration of the redox state, and increased activity of matrix metalloproteinases (MMPs). Thus, this study aims to evaluate aortic remodeling, MMP activity, and reactive oxygen species (ROS) levels after treatment with doxycycline in ApoE-⁄- and ovariectomized mice (OVX). Female ApoE-⁄--knockout mice (5 weeks) were submitted to ovariectomy surgery to induce experimental menopause. They then received chow enriched with 1% cholesterol to induce hyperchole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 72 publications
(107 reference statements)
0
4
0
Order By: Relevance
“…However, in a study involving female rabbits on a pro-atherogenic diet, long-term administration of NOS inhibitors caused chronic endothelial dysfunction which aggravated atherosclerosis. The protective effect of E2 was abolished in this setting in intact but not in de-endothelialized vessels (Rodrigues et al, 2022).…”
Section: The Role Of Endotheliummentioning
confidence: 75%
“…However, in a study involving female rabbits on a pro-atherogenic diet, long-term administration of NOS inhibitors caused chronic endothelial dysfunction which aggravated atherosclerosis. The protective effect of E2 was abolished in this setting in intact but not in de-endothelialized vessels (Rodrigues et al, 2022).…”
Section: The Role Of Endotheliummentioning
confidence: 75%
“…After menopause, women are more prone to have lipid metabolism disorders and higher levels of aortic ROS, 10,34 resulting in a microenvironment for increased levels of lipid peroxidation in the plaques, which may suggest an increased risk of ferroptosis in vascular resident cells. To test this hypothesis, we detected the levels of lipid peroxidation product 4‐HNE and MDA in the aortic plaque and plasma, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…13 Recently, the administration of ferroptosis inhibitor Fer-1 alleviated the dyslipidemia and aggravation of atherosclerosis in ApoE −/− mice, which contributed to the further study of the pathogenesis of atherosclerosis. 13 After menopause, women are more prone to have lipid metabolism disorders and higher levels of aortic ROS, 10,34 resulting in a microenvironment for increased levels of lipid peroxidation in the plaques, which may suggest an increased risk of ferroptosis in vascular resident cells. To test this hypothesis, we detected the levels of lipid peroxidation product 4-HNE and MDA in the aortic plaque and plasma, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Another mechanism associated with increased oxidative stress is the reduced bioavailability of endothelium-derived vasodilators. In a study conducted by Rodrigues [ 32 ], aortic remodeling, MMP activity, and ROS levels were assessed in apolipoprotein E ( ) and ovariectomized (OVX) mice treated with doxycycline. The findings indicated that the administration of doxycycline resulted in reduced levels of ROS, MMP-2 expression, and activity in /OVX mice, ultimately leading to a decrease in atherosclerotic lesions.…”
Section: Causes Associated With Vascular Remodelingmentioning
confidence: 99%